A new near-infrared fluorescent probe for sensing extreme acidity and bioimaging in lysosome. (1st April 2022) - Liu, Qiuchen; Liu, Chang; Cai, Songtao; He, Song; Zhao, Liancheng; Zeng, Xianshun; Zhou, Jin; Gong, Jin
Abstract: Since the intracellular pH plays an important role in the physiological and pathological processes, however, the probes that can be used for monitoring pH fluctuation under extreme acidic conditions are currently rare, so it is necessary to construct fluorescent probes for sensing pH less than 4. In this work, we developed a new near-infrared (NIR) fluorescent probe Cy-SNN for sensing pH fluctuation under extremely acidic conditions. For the preparation of this probe, benzothiozolium moiety was chosen as lysosomal targeting unit and NIR fluorophore, and barbituric acid moiety was fused in the polymethine chain of probe to introduce protonation center. Surprisingly, on the basis of the balance of quaternary ammonium salts and free amines, the pka value of Cy-SNN was calculated as low as 2.96, implying that Cy-SNN can be used in acidic conditions with pH < 4. Moreover, Cy-SNN exhibited highly selective response to H + over diverse analytes in real-time with dependable reversibility. Importantly, Cy-SNN can be used to specifically target lysosome, providing potential tools for monitoring the function of lysosome in autophagy process.